2017
DOI: 10.1080/08830185.2017.1291639
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of transforming growth factor-β in Wilms tumor immunopathogenesis

Abstract: Wilms tumor is the most common kidney malignancy in children, especially in children aged less than 6 years. Although therapeutic approach has reached successful rates, there is still room for improvement. Considering the tumor microenvironment, cytokines represent important elements of interaction and communication between tumor cells, stroma, and immune cells. In this regard, the transforming growth factor beta (TGF-β) family members play significant functions in physiological and pathological conditions, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…The dysregulation of TGF-β has been linked to the initiation and progression of multiple human cancers, including WT [18]. Several studies have demonstrated that the TGFβ signaling was activated by TGF-β; the ligands lead to the Negative expression of TGF-β1 and P-Smad2/3 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of TGF-β has been linked to the initiation and progression of multiple human cancers, including WT [18]. Several studies have demonstrated that the TGFβ signaling was activated by TGF-β; the ligands lead to the Negative expression of TGF-β1 and P-Smad2/3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric tumors, particularly WT, abnormally activated TGF-β signaling may be an important mediator of tumor cell growth, and the positive expression of TGF-β in WT was associated with tumor anaplastic, invasion, and disease progression [15][16][17]. Although TGF-β signaling played a key role in WT, the molecular mechanisms behind this regulation are unknown [18].…”
Section: Introductionmentioning
confidence: 99%
“… 62 Correspondingly, the tumor microenvironment of WT is also characterized by a high production of immunosuppressive cytokines, of which TGF-β appears to have the most dominant role in tumor progression. 62 , 63 , 64 , 65 Its role in kidney development and renal architecture control might explain its expression in a malignant kidney tumor. Moreover, high TGF-β levels are generally associated with epithelial-to-mesenchymal transition (EMT) mediated by E-cadherin downregulation.…”
Section: Cytokine Productionmentioning
confidence: 99%
“…64 A further tumor-promoting role of TGF-b in Wilms is the fact that this cytokine induces Forkhead box P3 (FOXP3) expression on T-reg cells. 65 This is a transcription factor known to be crucial in conferring immunosuppressive functions to the T-regs. 66 Correspondingly, FOXP3+ T-reg cells have been described to be diffusely present in WTs, and their infiltration is significantly higher than in control kidneys.…”
Section: Cytokine Productionmentioning
confidence: 99%
“…TGFBRI is a serine/threonine kinase receptor that is a member of the TGF-β signaling pathway, and exhibits metastatic properties by invading surrounding cells [13]. Previous reports have indicated that the TGF-β and IGF signaling pathways are associated with the development of nephroblastoma [14, 15]. However, the roles of TGFBRI and IGF1R in the progress of nephroblastoma require further investigation.…”
Section: Introductionmentioning
confidence: 99%